Tysker, fremmedarbejder eller østjysk mester? Nyt syn på fire krucifikser fra senmiddelalderen - Andersen, Britta (Hikuin, 1999)
German, foreign worker or local master. Four late medieval crucifixes in a different light By Britta Anzdersen Danish research in late medieval wooden sculpture has almost only dealt with high quality works of art, while less beautiful and well preserved pieces have been neglected. Over the years the prevalent attitude to the late medieval sculpture has been that high quality is due to import while low quality is supposed to have been produced in local workshops. This tradition is the theme of discussion in the present article, and the conclusion is that it is the amount of identical sculptures in a certain area and the fact that nothing quite like it can be found anywhereelse that decides where it has been produced. In other words it is not just the quality of the wooden sculpture that speaks for import versus local production. Furthermore the article argues for a different dating of four crucifixes from the east part of Jutland.